Qur'anic Morality in the Text of Serat Pamardining Siwi Wira Iswara KBG 702 - Khusniyah, Aziizatul; Ahmad, Nur (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2022)
Discussing the values of character education basically involves efforts that are consciously realized to improve attitudes or morals. This paper aims to explain the values of character education in the Serat (script)of Pamardining Siwi Wira Iswara KBG 702, later known as script of Wira Iswara (WI). This is also to see its relevance in the teachings of the Qur'an, through a textual and contextual understanding study. The focus of this research is how the value of character education is in the Wira Iswara script which has relevance to the Qur'an. The method used is qualitative with a philological approach. The research data were then analyzed using content analysis. The results of this study indicate that the value of character education contained in Wira Iswara script is derived from the values of the Qur'an which include: 1) the value of mutual love or affection, 2) agile, 3) careful, 4) careful, 5) good at counting, 6) diligent, 7) frugal, and 8) seriousness of intention or earnest. These values are qur'ani morality that is implicitly recorded in the Wira Iswara manuscript.